A Frenchwoman Writes about Indochina, 1931-1949: Andrée Viollis and Anti-colonialism - Stewart, Mary (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
Abstract“A Frenchwoman Writes about Indochina, 1931-1949: Andrée Viollis and Anti-colonialism” examines investigative reporter Andrée Viollis’ journalistic career, especially her articles and books on French and other European colonies between 1922 and 1935, in order to challenge recent postcolonial critiques of her 1935 book, Indochine S.O.S, as immured in colonial ideology and rhetoric, including a kind of patriarchal feminism, despite being an exposé of colonial abuses and sympathetic to indigenous rebels against the colonial regime. Following the lines of recent critiques of postcolonial cultural approaches for inattention to the material conditions of colonialism, and feminist transnational scholars who attempt to link labour conditions in the “First World” to those in the “Third World,” The article establishes Viollis’ credentials as a liberal, not a maternal or patriarchal feminist, analyses her journalistic style, especially her use of indirect suggestion as a reporter in the popular daily press, and describes the interest in the colonies in the French public and press. Next the article describes Viollis’ colonial reporting and publications from the 1920s through 1935, with special attention to her exposés of economic exploitation in British and French colonies. Third, the article examines the evidence cited in postcolonial critiques of Viollis’ advocacy of equality between colonizers and colonized as mere equality between people of the same social class, her portrayal of indigenous Vietnamese as degraded, her belief that the French or French women should be moral tutors of the uncivilized natives, and finally her portrayal of indigenous peoples as degraded and animalistic, in light of a full analysis of her career and book. After a detailed analysis of her position on equality, morality, and the condition of peasants and workers up to and in the book, the articles rejects the evidence as partial and decontextualized, and the interpretation as unfamiliar with Viollis’ style.